Coping Community, Collective Posttraumatic Growth and Social Well-Being in Context February 27 Earthquake in Chile, 2010 [Afrontamiento Comunal, Crecimiento Postraumático Colectivo y Bienestar Social en el Contexto del Terremoto del 27 de Febrero de 2010 en Chile] - Wlodarczyk, A (Sociedad Chilena de Psicologia Clinica, 2014)
The earthquake and tsunami in Chile on February 27, 2010 constituted a context of disaster which mobilized collective strategies to cope with its effects. One of them corresponds to the communal coping (CC), which involves activating social resources to solve shared collective problems. Another aspect is the reevaluation associated with positive changes that people perceive after a disaster and it is defined as post-traumatic growth (PTG). This paper explores the use of different forms of CC and PTG after the earthquake, in a sample of 80 people in Chile. Four dimensions of communal coping were identified: direct coping, distraction, emotional expression and avoidance. Furthermore, PTG structure was defined as composed of individual, relational and collective levels. Direct coping, distraction and emotional sharing significantly correlated with CPT and social well-being. The results and their implications are discussed in a context of psychosocial studies of natural disasters. 2014 by Sociedad Chilena de Psicología Clínica